Determinación del coeficiente de endurecimiento por deformación en una aleación de aluminio y un acero estructural ASTM A500 (2024)
This project aims to determine the strain hardening coefficient for two materials, a commercial aluminum alloy and an ASTM A500 steel, through tensile tests in a universal testing machine. In order to obtain the necessary calculations to determine the parameter, the ASTM E 646 standard was studied together with the ASTM E8 standard and several concepts necessary to develop the project. The tests were carried out in the laboratories of the University of America, with the help of a universal testing machine, the force and displacement values ​​of the commercial aluminum and ASTM A500 steel test specimens were obtained.